PENGARUH MODEL PEMBELAJARAN PROJECT CITIZEN BERBASIS CANVA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI MTs AL-WASHLIYAH PEMATANGSIANTAR - Fatimah Az-Zahra; Surya Dharma; Sri Yunita; Liber Siagian; Hapni Laila Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Canva-based Project Citizen learning model on the learning outcomes of class VIII students of MTs Al-Washliyah Pematangsiantar. This type of research uses a quantitative approach to determine the causal relationship between the independent variable of Canva-based Project Citizen and the dependent variable of Learning Outcomes, so the research design used is Quasi Experiment with a nonequivalent control group design. This study uses data collection techniques, namely learning outcome tests, questionnaires, documentation studies and observations. This research was conducted at MTs Al-Washliyah Pematangsiantar. The students of class VIII-1 and VIII-2. The data were analyzed statistically with a t-test, then a normality test, a homogeneity test and a hypothesis test were carried out with a paired t-test and an independent sample t-test. The results showed that the Canva-based Project Citizen learning model had a significant effect on improving the learning outcomes of class VIII-2 students and had differences in learning outcomes between students in the experimental class and the control class. It can be seen from the results of the experimental class mean which was initially 44.50 to 87.75. This difference was strengthened through the results of the Wilcoxon statistical test, the data showed the Asymp. Sig. value. (2-tailed) of 0.000, meaning <0.05. The difference in mean learning outcomes before and after the treatment was truly significant. The experimental class achieved a mean post-test score of 87.75, while the control class showed only limited improvement with a mean post-test score of 66.75. This difference was confirmed by the results of the Mann-Whitney test, which produced a significance value (Asymp. Sig. 2-tailed) of 0.000, meaning <0.05. The difference in learning outcomes between the two sample groups was truly significant. Keywords: Learning Outcomes, Pancasila Education, Canva-based Project Citizen